(untitled) (Journal of the College of Basic Education, 2022)
This study was conducted using polyurethane as a basic material (a binder that binds reinforcing materials and transmits forces to them, and rock wool as a reinforcing material to obtain a superimposed material resulting from the joining of two materials for the purpose of obtaining a new material with suitable properties that combines the properties of the two materials.